Effective Removal of Nitrate, Nitrite, Ammonia and Iron from Contaminated Ground Water using Bio-Sand Method and Sponge Layer Filtration Method - Homagai, Puspa Lal; Poudel, Sujan (Journal of Nepal Chemical Society, 2018)
Available with full text